The role of RhoJ in endothelial cell biology and angiogenesis. (21st November 2011) - Leszczynska, Katarzyna; Kaur, Sukhbir; Wilson, Eleanor; Bicknell, Roy; Heath, Victoria L.
Abstract : RhoJ is an endothelially expressed member of the Cdc42 (cell division cycle 42) subfamily of small Rho GTPases. It is expressed in both the developing mammalian vasculature and the vascular beds of a number of adult tissues, with its expression regulated by the endothelial transcription factor ERG (ETS-related gene). RhoJ has been shown to regulate endothelial motility, tubulogenesis and lumen formation in vitro, and modulates the vascularization of Matrigel plugs in vivo . Both vascular endothelial growth factor and semaphorin 3E have been found to affect its activation. RhoJ has been shown to be a focal-adhesion-localized Rho GTPase which can modulate focal adhesion number, actomyosin contractility and activity of Cdc42 and Rac1. The present review discusses the biology of RhoJ with a focus on recent reports of its role in endothelial cells and angiogenesis.